Effective Combination of Photodynamic Therapy and Imiquimod 5% Cream in the Treatment of Actinic Keratoses: Three Cases. (27th December 2012) - Held, Laura; Eigentler, Thomas Kurt; Leiter, Ulrike; Garbe, Claus; Berneburg, Mark-Jürgen
Abstract : Background . The therapy for actinic keratoses includes photodynamic therapy (PDT) and imiquimod 5% cream. The sequential use of both could result in better clinical outcomes. Objectives . To enhance efficacy of therapies while improving tolerability, convenience, and patient adherence with a scheme combining two concomitant or sequential AK treatments. Methods . All patients underwent one session of conventional PDT. Two weeks after, the PDT imiquimod 5% cream was applied to the treatment area once daily for three days per week. One course continued for four weeks followed by a clinical evaluation and decision about further treatment. Patients who had not cleared all of their AK lesions in the treatment area in course 1 participated in a second 4-week course of treatment. Limitations . Small size of population. Results . Three participants were enrolled. Two patients showed complete clinical clearance of AKs. The effect was also noted after long-term followup, at months seven and eleven. No subject discontinued for an adverse event. There were severe local skin reactions in two participants which were severe erythema, scaling, and crusting. One patient showed no response to the therapy. Conclusions . Photodynamic therapy followed by imiquimod was well tolerated and improved reduction of actinic keratoses. This initial proof-of-concept should be studied in larger clinical trials.